CONTRIBUTION TO CREATION OF MULTIMEDIA MATERIALS SUPPORTING FOREIGN LANGUAGE TEACHING - HASKOVA, Alena; ZAHOREC, Jan (Trends in education, 2008)
The article presents four language electronic expository dictionary of special terms related to lexicology and theory of instruction. The dictionary is intended for philogogists and teacher trainees' specific language training at universities. It has been developed as an integral part of the KEGA project 3/402/06 Utilization of Information and Communication Technologies at Teaching Materials Development in University Foreign Language Teaching which is solved by Constantine the Philosopher University in Nitra in co-operation with Trnava University.
Keywords: multimedia assisted teaching; specific target group foreign language preparation; lexicology; theory of instruction; expository dictionary